Pengaruh Stres Kerja, Konflik Kerja Dan Lingkungan Kerja Terhadap Semangat Kerja Pada Karyawan UD. Harum Manis Kota Tebing Tinggi - Jayanti, Suci Etri; Damanik, Sri Winda Hardiyanti; Zurlaini, Ayu; Mulyani, Sri (Management And Business Progress, 2025)
This study aims to determine "The Influence of Work Stress, Work Conflict and Work Environment on Work Enthusiasm in UD Employees. The Sweet Fragrance of Tebing Tinggi City.” The method of determining the sample used in this study is the Quantitative method. The sampling technique a total sampling technique of 60 samples which are all UD employees. The Sweet Fragrance of Tebing Tinggi City. Based on the results of the analysis the first hypothesis is accepted, meaning that the work stress variable (X1) influences the work morale variable (Y). The results of the analysis of hypothesis 2 can be concluded that the second hypothesis is accepted, meaning that the Work Conflict variable (X2) influences the Work Morale variable (Y). And the results of the analysis of hypothesis 3 can be concluded that the third hypothesis is rejected, meaning that the Work Environment variable (X3) has no effect on the work morale variable (Y). Based on the results of the analysis of hypotheses 4 it can be concluded that hypotheses 1, 2 and 3 are accepted, meaning that the variables Job Stress (X1), Work Conflict (X2) and the environment simultaneously influence the work morale variable (Y).